Phylogenetic analyses reveal bat communities in Northwestern Mexico harbor a high diversity of novel cryptic ectoparasite species - Laura A. Najera‐Cortazar; Alex Keen; Thomas Kitching; Drew Stokes; Simon J. Goodman (Ecology and Evolution, 2023)
Abstract Parasites are integral parts of ecosystem function and important drivers of evolutionary processes. Characterizing ectoparasite diversity is fundamental to studies of host–parasite interactions, evolution, and conservation, and also for understanding emerging disease threats for some vector borne pathogens. With more than 1400 species, bats represent the second most speciose mammalian clade, but their ectoparasite fauna are poorly known for most species. We sequenced mitochondrial Cytochrome Oxidase C subunit I and nuclear 18S ribosomal gene fragments, and used Bayesian phylogenetic analyses to characterize ectoparasite taxon identity and diversity for 17 species of parasitized bats sampled along the Baja California peninsula and in Northwestern Mexico. The sequence data revealed multiple novel lineages of bat bugs (Cimicidae), flies (Nycteribiidae and Streblidae), and ticks (Argasidae). Within families, the new linages showed more than 10% sequence divergence, which is consistent with separation at least at the species level. Both families of bat flies showed host specificity, particularly on Myotis species. We also identified new records for the Baja peninsula of one tick (Carios kelleyi), and of five Streblid bat fly species. One Nycteribiid bat fly haplotype from Pallid bat (Antrozous pallidus) hosts was found throughout the peninsula, suggesting potential long distance co‐dispersal with hosts. Different bat bug and tick communities were found in the north and south of the peninsula. This study is the first systematic survey of bat ectoparasites in the Baja California peninsula, revealing novel lineages that are highly genetically differentiated from other parts of North America. For some ectoparasite species, haplotype distributions may reflect patterns of bat migration. This work is a first step in characterizing ectoparasite diversity over the Baja California peninsula, and understanding how ecological and evolutionary interactions shape bat ectoparasite communities among host species in different parts of their ranges.